Treasury Bill Pricing in the Spot and Futures Markets - Capozza, Dennis R.; Cornell, Bradford (The Review of Economics and Statistics, 1979)
STUDIES of the term structure of interest rates have a long tradition in the literature of finance and economics. Two prominent examples are Roll (1970) and Nelson (1971).1 More recently, a parallel literature has evolved on the pricing of commodity contracts, spawned by the work of Dusak (1973) and Black (1976). With the advent of futures trading in Treasury bills on the Chicago Mercantile Exchange (CME) the direct relationship between the theory of the term structure of interest rates and the theory of commodity contract pricing has become apparent. Since arbitrage is possible between the spot and futures markets, appropriately defined returns in both markets should be identical. In this paper we compare the returns in the spot and futures markets over the first 30 months of trading in the CME Treasury bill futures market. Surprisingly, we find that rather large deviations between returns in the two markets have persisted throughout the sample period, i.e., the one price law is violated. For this result to be obtained, arbitrage costs must be large, differential risk must exist, or traders in the two markets must be distinct non-overlapping groups. In the next section an arbitrage condition connecting the two markets is derived. The condition specifies the relationship between returns in the spot and futures markets under the assumption of a perfect capital market. The third section presents the data and demonstrates that the arbitrage condition has not been satisfied. The fourth section offers a possible explanation for the failure of the arbitrage condition. The paper concludes with a summary of the results.